2001
DOI: 10.1039/b009104i
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermosensitive core–shell colloids by small-angle neutron scattering including contrast variation

Abstract: We present an investigation of thermosensitive coreÈshell particles by small-angle neutron scattering (SANS). The particles consist of a solid poly(styrene) core and a shell of crosslinked poly(N-isopropylacrylamide) (PNIPA) chains. These latex particles are dispersed in water and have a diameter of ca. 150 nm. At ambient temperature the PNIPA-network in the shell is swollen but at higher temperature water is expelled and the shell undergoes a continuous volume transition. The radial extension of the shell is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 22 publications
8
96
0
2
Order By: Relevance
“…18 A comprehensive characterization of these particles has been done recently by a combination of small-angle x-ray scattering ͑SAXS͒ and small-angle neutron scattering ͑SANS͒. 45,46 The main result of this work was to show that the shell of these core-shell particles is rather compact. This can be traced back to the method of polymerization.…”
Section: A Synthesis and Characterization Of The Particlesmentioning
confidence: 94%
“…18 A comprehensive characterization of these particles has been done recently by a combination of small-angle x-ray scattering ͑SAXS͒ and small-angle neutron scattering ͑SANS͒. 45,46 The main result of this work was to show that the shell of these core-shell particles is rather compact. This can be traced back to the method of polymerization.…”
Section: A Synthesis and Characterization Of The Particlesmentioning
confidence: 94%
“…Moreover, an analysis of these particles by a combination of small-angle neutron and X-ray scattering revealed that the shell is well-defined and the particles exhibit a narrow size distribution 32,33 . Their interaction in water is purely repulsive 31 if the temperature is not raised over 30 0 C.…”
Section: Comparison Of Model Calculations and Experimental Data mentioning
confidence: 99%
“…In particular, they can be studied in great detail using contrast-variation methods, 24 achieved most readily in the context of small-angle neutron scattering (SANS), although several studies make use of light [25][26][27] or X-ray [28][29][30] http://doc.rero.ch Through contrast variation, via the variation of scattering contrast by selective isotopic substitution of protons for deuterium in SANS, small-scale structures can be discriminated. This has been amply demonstrated in the past for, e.g., polymer-coated particles, [31][32][33] self-assembled surfactant [34][35][36][37] and block copolymer [38][39][40][41] systems. In addition, the quantitative modeling of SANS data for the same system under variable contrast is a far more stringent test of the models used and can therefore deliver more reliable values for structural parameters.…”
Section: Introductionmentioning
confidence: 99%